Kewenangan Penyelesaian Sengketa Ekonomi Syariah Pasca Uu No. 3 Tahun 2006 Tentang Peradilan Agama - Maulana Ira (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
This study aims to describe the issuance of Law Number 3 of 2006 concerning the Religious Courts which has increased the authority of the Religious Courts. The mandate of the law instructs religious courts to not only accept, examine, decide, and adjudicate marriage and inheritance cases, but also have the authority to resolve sharia economic disputes. This research uses a normative juridical research method. Normative juridical research is research that examines various laws and regulations that apply or are applied to a particular legal problem. Normative juridical law research is often referred to as doctrinal law research. From the results of this study, it is explained in the explanation of article 49 letter (i) of Law Number 3 of 2006 concerning Religious Courts. This indicates that apart from the religious judiciary, it is not allowed to accept, examine, decide, and adjudicate sharia economic cases. The absolute authority of the religious court has been patented by the decision of the Constitutional Court no. 93/PUU-X/2012 which stipulates that sharia economic disputes are the absolute authority of the religious courts. The Constitutional Court's decision at the same time eliminates dualism in the judicial environment to resolve sharia economic dispute cases. Keywords: Sharia Economic Disputes, Religious Courts, Authority